2018
DOI: 10.18632/oncotarget.25090
|View full text |Cite
|
Sign up to set email alerts
|

Could a plant derived protein potentiate the anticancer effects of a stem cell in brain cancer?

Abstract: Glioblastoma is the most aggressive brain tumor with poor overall survival bellow 2 years. The natural compounds with anti-cancer properties, are thus gaining attention for possible adjuvant GBM treatment. In various cancer models Enterolobium contortisiliquum Trypsin Inhibitor (EcTI) proved to have anti-cancer effects. Here, we investigated the EcTI effects on GBM U87 cells and on mesenchymal stem cells (MSC) compared to their direct coculture (MSC/U87). MSC are present in tumor stroma, modulating GBM cells p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
5
1
1
Order By: Relevance
“…The decrease of total cell viability, as shown in Figure 1A, in cocultured cells at 24 h is thus due to dying MSCs, as these cells were more vulnerable to the apoptotic effect of the inhibitor, as one would expect (Figure 1B). Interestingly, these results are in contrast to our previous experiments with another protease inhibitor (EcTI), isolated from Enterolobium contortisiliquum , also of the same Kunitz-type family, but having no lectin-binding properties [30]. EcTI did not cause U87 cell death, neither in mono, nor in coculture, suggesting that the proteolysis inhibition per se does not play a role in apoptosis.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The decrease of total cell viability, as shown in Figure 1A, in cocultured cells at 24 h is thus due to dying MSCs, as these cells were more vulnerable to the apoptotic effect of the inhibitor, as one would expect (Figure 1B). Interestingly, these results are in contrast to our previous experiments with another protease inhibitor (EcTI), isolated from Enterolobium contortisiliquum , also of the same Kunitz-type family, but having no lectin-binding properties [30]. EcTI did not cause U87 cell death, neither in mono, nor in coculture, suggesting that the proteolysis inhibition per se does not play a role in apoptosis.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, the adhesion of MSC and U87 cells alone to three ECM-related substrates remained unaltered upon CrataBL treatment, but was inhibited in U87 coculture pretreatment, especially with laminin, where the adhesion was significantly decreased at a higher (100 μM) CrataBL concentrations. CrataBL more effectively decreased U87 cell adhesion compared to the other Kunitz-type inhibitor, EcTI, which only slightly decreased the adhesion of U87 cells to fibronectin and MSC cocultured U87 cells to collagen IV [30]. CrataBL seems to interact in a more complex manner with cells to impair their adhesion to extracellular matrix components than EcTI.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inhibitors derived from Bauhinia bauhinioides , BbKI (human plasma kallikrein inhibitor) and BbCI (cruzipain inhibitor), were investigated in models of inflammation and reperfusion [ 10 , 17 ], venous and arterial thrombosis of mice [ 13 ], a prostate cancer model [ 18 ], cell invasion and angiogenesis in different cell lines [ 12 ], a pulmonary emphysema model in mice [ 14 ], and as a potential insecticidal agent [ 19 ]. EcTl, a trypsin inhibitor derived from Enterolobium contortisiliquum , was investigated in gastric cancer [ 11 ], triple-negative breast cancer [ 20 ], glioblastoma [ 21 , 22 ], the reduction of inflammation and pulmonary remodeling in induced lung inflammation [ 23 ], and in an asthma model [ 24 ]. In addition, EcTI was investigated in non-tumorigenic cells such as human mesenchymal cells [ 25 ] and showed no effects, demonstrating the potential use of these compounds as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, some bacteria can convert amino acids in nitrosamines and induce DNA alkanisation and mutations (Kim, Lee, Jung, & Kim, 2017; Ma, Tian, Wu, & Ma, 2017; Sasso & Latella, 2018; Zaramela et al, 2019). In contrast, a low‐protein diet was shown to activate immune responses to inhibit the growth of mouse lymphoma, melanoma, and colorectal cancer (Rubio‐Patiño et al, 2018), while the plant‐derived protein (Bonturi et al, 2018; Møller et al, 2019), in particular, the fungal proteins from some mushrooms have been shown to have an effective immunomodulatory effect (Akanbi, Post, & van Putten, 2013; Hassan, Rouf, Tiralongo, May, & Tiralongo, 2015; Hsin et al, 2011), and improvement on gut microbiota (Chen et al, 2017). Dietary fiber can be metabolized by the gut microbiota, and the metabolites can prevent cancer; low fiber intake can cause gut microbiota disorders, leading to many diseases, including colon cancer (Bishehsari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%